Service science : the foundations of service engineering and management - Qiu, Robin G.; Wiley eBooks (Hoboken, New Jersey : Wiley, 2014)
"By relying on the recent development of service science, this book focuses on the science of implementing a service system throughout its lifecycle, spanning from service marketing, engineering, delivery, quality control, management, to further improvement. The author utilizes a combined theoretical and practical approach to discuss the field of service science. Driven by today's new business environment, including advanced computing and telecommunications, accelerated business globalization, increased automation, and highly on-demand and competitive innovations, emphasis on the service sector has evolved to sources of innovations, collaboration, and value co-creation to optimally and cost-effectively meet the needs of end users, i.e. satisfaction, success, and profitability. Leading and competitive services enabled by service systems are all remarkably delineated by people-centric, information-driven, e-oriented, and satisfaction/success-focused characteristics. Compared to the mature knowledge of goods-producing business practices, service science is developing innovative, new constructs for mathematical modeling, process design, marketing, resource-revenue-risk management, and strategy. The book contains six parts: the evolution of services; service systems physics; market and service design; engineering and operations; delivery and service quality; and sustainment and improvement. By eliminating theoretical dependencies of each part, the book can also be tailored for students with different backgrounds and expectations. As opposed to typical course books where problems and exercises are used to help readers digest covered subjects, this book heavily relies on case studies to show how the presented theories and design principles are applied in practice, making it more suitable for students and professionals to master the foundations of service management"--
"As a reference and or self-study for academics, professionals, and researchers in applied mathematics, statistics, business/management science, operations research, industrial engineering, and economics; as a textbook for MBA students interested in understanding service management; appropriate as a textbook for upper-level undergraduate and graduate students"--
Includes bibliographical references and index.
Machine generated contents note: Foreward Preface Acknowledgements Biography Chapter 1. Evolving and Holistic View of Services 1.1 What is Service? 1.2 Different Perspectives on Service 1.3 The Lifecycle of Service 1.4 Service Encounters throughout the Lifecycle of Service 1.5 The Economy Globalization 1.6 The Evolving and Holistic View of Service 1.7 Summary Chapter 2. Definition of Service 2.1 From Manufacturing to Service: the Economic Shift 2.2 Total Service Lifecycle: the Service Provider's Perspective 2.3 A Service Definition for This Book 2.4 Chapter Final Remarks Chapter 3. The Need for the Science of Service 3.1 A Brief Review of the Evolution of Service Research 3.2 Service as a Process of Transformation 3.3 Formation of Service Encounters Networks 3.4 Constituting Socio-Technical Service Systems 3.5 Digitalization of Service Systems 3.6 An Innovative Approach to Exploring Service Science Chapter 4. Service Science Fundamentals 4.1 The Fundamental Laws of Service: A Systemic Viewpoint 4.2 The Service Encounter Socio-physics 4.3 Service Science: a Promising Interdisciplinary Field 4.4 Conclusion Chapter 5. Organizational and IT Perspectives of Service Systems and Networks 5.1 Service as an Offering of a Service System 5.2 Putting People First 5.3 Controllable and Tractable Service Systems in Pursuit of Smarter Operations 5.4 Competitiveness, Sustainability, and Innovation : Systems Approaches to Exploring the Socio-Technical Natures of Service Systems and Networks 5.5 Final Remarks Chapter 6. Computational Thinking of Service Systems and Networks 6.1 Monitoring and Capturing People-centric Service Network Dynamics in Real Time 6.2 Computational Thinking of Service Systems 6.3 Modeling of a Configurable and Competitive Service System 6.4 Service Systems' Performance: Metrics and Measurements 6.5 PDGroup as an Exploratory Example of Service Systems Modeling 6.6 Conclusions Chapter 7. Education as a Service and Educational Service Systems 7.1 Systems of Schooling: Service Science's Perspective 7.2 Off-campus Learning: An Example of High School STEM Education Enhancement 7.3 A Quality Control and Management Case Study for Resident Education: the Systems Perspective 7.4 A Lifecycle and Real-time based Approach to Service Engineering and Management 7.5 Summary Chapter 8. Online Education Service and MOOCs 8.1 Introduction 8.2 A Systemic Approach to Analyzing Collaborative Learning 8.3 Collaborative Leaning Analytics: Part I 8.4 Collaborative Leaning Analytics: Part II 8.5 Conclusions Chapter 9. The Science of Service Systems and Networks 9.1 The Science of Service Systems and Networks 9.2 The Science of Service in the 21st Century .
John Wiley and Sons
Keywords: Service industries; Service life (Engineering); Industrial engineering; TECHNOLOGY & ENGINEERING / Operations Research; TECHNOLOGY & ENGINEERING / Industrial Engineering; Industrial engineering; Service industries; Service life (Engineering); Service industries; Service life (Engineering); Industrial engineering; Electronic books